Al-Amtsāl as a Cognitive Bridge for Understanding Faith in Angels Among Elementary School Students - Awan Setiawan; Ridwan; Lia Marliana (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the use of al-amtsāl in teaching faith in angels at the elementary school level and to explain its role as a cognitive mediation mechanism that supports students’ understanding of unseen concepts in Islamic creed learning. Methodology: This study employed a qualitative approach using a case study design conducted at SDN Binakarya 1 Banyuresmi Garut, Indonesia. Participants included elementary school teachers and students. Data were collected through classroom observations, semi-structured interviews, and document analysis. The collected data were coded and analyzed using thematic analysis techniques to identify recurring patterns and categories. Main Findings: The findings reveal that teachers employed al-amtsāl through existential, functional, and visual analogies to connect the concept of angels with students’ concrete experiences. These analogies facilitated cognitive mediation by linking prior knowledge with unseen concepts, enabling students to construct meaning through experience-based understanding and analogical reasoning. The findings also indicate that this approach improved students’ comprehension of abstract theological concepts in aqidah learning contexts. Novelty/Originality of this study: This study offers an initial conceptualization of an al-amtsāl-based pedagogical model for teaching unseen concepts in Islamic education, derived from an elementary school case study. It contributes to the literature on Qur’anic pedagogy by positioning al-amtsāl as a cognitive bridge that mediates students’ understanding of abstract theological concepts through experience-based analogical learning. The findings provide preliminary insights into integrating cognitive and theological dimensions in elementary Islamic education.